Pengaruh Intervensi Pill Box dan Medication Chart Terhadap Kepatuhan Dan Luaran Klinis Pasien Diabetes Mellitus Tipe 2 di Puskesmas Susukan - Nurul Izha Arisqa; Siti Setianingsih; Silma Kaaffah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Type 2 Diabetes Mellitus (T2DM) is a major non-communicable disease in Indonesia with high morbidity and mortality. Poor adherence to antidiabetic medication is a key factor contributing to inadequate glycemic control. Practical tools such as pill boxes and medication charts have been developed to support patients in following prescribed therapy. This study aimed to evaluate the effectiveness of pill boxes and medication charts in improving medication adherence and clinical outcomes, specifically fasting blood glucose (GDP) and random blood glucose (GDS), among T2DM patients at Susukan Public Health Center. A quasi-experimental pre-test and post-test design with a control group was applied. Ninety respondents were recruited using total sampling and divided equally into pill box, medication chart, and control groups. Medication adherence was assessed using the Medication Adherence Rating Scale-10 (MARS-10), while GDP and GDS levels were measured using a glucometer. Data were analyzed with paired t-tests, Wilcoxon tests, and intergroup comparisons at a 5% significance level. Results showed significant improvement in adherence in both intervention groups compared to the control (p<0.05). In the pill box group, mean GDP decreased from 157.23 ± 53.21 mg/dL to 126.76 ± 14.82 mg/dL (p=0.000), while in the medication chart group it decreased from 162.66 ± 24.89 mg/dL to 145.66 ± 26.54 mg/dL (p=0.006). No significant change was seen in the control group (p=0.741). For GDS, a significant reduction was found only in the pill box group (p=0.005). In conclusion, both pill boxes and medication charts improved adherence among T2DM patients, with pill boxes providing greater benefit for glycemic control. These low-cost, practical strategies are recommended for routine use in primary healthcare to enhance diabetes management.are recommended for integration into primary healthcare services to optimize diabetes management.